The Problem of Humanism in J. G. Fihte’s Philosophy - Asatryan, Grigor (Bulletin of Yerevan University E: Philosophy, Psychology, 2014)
The article is an attempt to comprehend Fihte’s humanism (1762-1814). The gist and the specific features of Fihte’s humanism, which determine the special place of his humanism in the evolution of both German classic humanism and the world humanistic legacy as a whole are analyzed. We also underscore that some of Fihte’s fundamental humanistic principles and ideas have not lost their freshness and are no less valid and actual today than in the days of the great German thinker and humanist.